Hematological Indices of Pesticide Exposure Rice Farmers in Southern Thailand - Kwanhian, Wiyada; Yimthiang, Supabhorn; Jawjit, Siriuma; Mahaboon, Junjira; Vattanasit, Udomratana; Thirarattanasunthon, Phiman (UI Scholars Hub, 2019)
The most common pesticides used in rice farming are organophosphates and carbamates. These pesticides inhibit acetylcholinesterase (AChE) activity, resulting in excessive levels of acetylcholine accumulation and disrupted neurotransmission. This study compared AChE activity and hematological parameters between pesticide-using rice farmers, non-pesticide using rice farmers, and non-agricultural occupational groups (non-farmers). Pesticide residues that accumulated in rice and the water and soil of the study area were also determined. AChE activity of all participants showed 10 from 87 samples (11.49%) as borderline depressed, with 50% of these being pesticide-using farmers. Most of the hematological parameters were normal in all samples. However, platelet numbers of pesticide self-spraying rice farmers were significantly lower than non-self-spraying rice farmers. The results suggested that the use of pesticides during rice farming affected AChE activity and some hematological cells. In addition, pesticide residues in soil, water and rice in rice fields using pesticides were higher than in non-pesticide use areas. Results confirmed that the exposure rates of farmers using pesticides were at higher risk than farmers who did not use pesticides